2021
DOI: 10.5937/jpea25-33591
|View full text |Cite
|
Sign up to set email alerts
|

Biological nutritional value of zeolite-based soil enhancers

Abstract: A series of greenhouse experiments were conducted in order to determine the biological nutritional value of the substrate mixtures based on newly designed zeolite soil enhancers made to replace an earlier registered commercial enhancer (ZeoPlant™). Lettuce (Lactuca sativa L.) was used as a test species. Plant height, number of leaves, and fresh plant mass were measured. During the preliminary experiments, the optimal ratio of enriched zeolites in the peat-based substrate mixtures was verified (about 25% volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Furthermore, various studies, including those by Atif et al (2016), Damjanović et al (2005), Gutierrez-Miceli et al (2007), Herrera et al (2008), and Ugrinović et al (2018), have confirmed the significant impact of substrates on the growth and quality parameters of seedlings. Proper substrate selection is crucial for growers to produce high-quality seedlings (Gutierrez-Miceli et al, 2007;Herrera et al, 2008;Morales-Corts et al, 2014;Atif et al, 2016;Ugrinović et al, 2018;Ugrinović et al, 2021). Many studies have also confirmed that the total number of leaves per plant depends on the nutritional regime of the substrate, water regime, and other ecological factors.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, various studies, including those by Atif et al (2016), Damjanović et al (2005), Gutierrez-Miceli et al (2007), Herrera et al (2008), and Ugrinović et al (2018), have confirmed the significant impact of substrates on the growth and quality parameters of seedlings. Proper substrate selection is crucial for growers to produce high-quality seedlings (Gutierrez-Miceli et al, 2007;Herrera et al, 2008;Morales-Corts et al, 2014;Atif et al, 2016;Ugrinović et al, 2018;Ugrinović et al, 2021). Many studies have also confirmed that the total number of leaves per plant depends on the nutritional regime of the substrate, water regime, and other ecological factors.…”
Section: Resultsmentioning
confidence: 99%